2000
DOI: 10.1016/s0014-5793(00)02149-9
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of singlet oxygen by carotenoids produced in Escherichia coli – attenuation of singlet oxygen‐mediated bacterial killing by carotenoids

Abstract: We examined the viability of Escherichia coli transformants harboring various carotenoids synthesizing genes in a medium containing an enzymatic singlet oxygen generating system, which contained myeloperoxidase, hydrogen peroxide and Br 3 at pH 4.5. Singlet oxygen quenching activities of various carotenoids in phosphatidyl choline micelles in aqueous media were also studied using the same enzymatic singlet oxygen generating system. Viability of the transformants producing carotenoids was higher than that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 41 publications
0
42
0
1
Order By: Relevance
“…A role of membrane carotenoids in quenching 1 O 2 * also has been demonstrated in nonphotosynthetic bacteria (Tatsuzawa et al, 2000) and fungi (Schroeder and Johnson, 1995). In animals, zeaxanthin and lutein are thought to have important antioxidant functions (Mares-Perlman et al, 2002).…”
Section: How Does Zeaxanthin Accumulation Protect Cells From Photooximentioning
confidence: 97%
“…A role of membrane carotenoids in quenching 1 O 2 * also has been demonstrated in nonphotosynthetic bacteria (Tatsuzawa et al, 2000) and fungi (Schroeder and Johnson, 1995). In animals, zeaxanthin and lutein are thought to have important antioxidant functions (Mares-Perlman et al, 2002).…”
Section: How Does Zeaxanthin Accumulation Protect Cells From Photooximentioning
confidence: 97%
“…Carotenoids are efficient scavengers of ROS, especially of singlet oxygen ( 1 O 2 ) and peroxyl radicals (ROO ⅐ ) (587,608).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Jayaraj and Punja reported that the transgenic carrot plant expressing the algal ␤-carotene ketolase gene accumulated various ketocarotenoids, including astaxanthin, and exhibited remarkable resistance to UV-B irradiation and oxidative stress in comparison with the wild-type carrot (13). Further, Escherichia coli transformant cells were reported to acquire tolerance to oxidative stress by the introduction of carotenoid synthetic genes (27). During fermentation processes, yeast cells are exposed to various stresses, including high concentrations of ethanol, high temperature, and high osmolarity, which generate ROS (8)(9)(10)21).…”
mentioning
confidence: 99%